Implementasi Metode Talaqqi dan Mutaba’ah dalam Menghafal Al-Qur`an di Rumah Tahfizh Madani Tanjung Bonai Aur - Kesuma, Jihan; Hafizzullah, Hafizzullah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to examine and describe the implementation of the talaqqi and mutaba’ah methods in Qur’an memorization at Rumah Tahfizh Madani Tanjung Bonai Aur. The research questions focus on: (1) how the talaqqi and mutaba’ah methods are applied in the memorization process, (2) the advantages and disadvantages of each method, and (3) their influence on students’ memorization outcomes. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the talaqqi method is implemented by having the teacher recite verses which are then repeated by the students, followed by direct correction during recitation sessions, with evaluation conducted through tasmi’ and testing. Meanwhile, the mutaba’ah method requires students to memorize independently before reciting to the teacher for correction, with similar evaluation procedures. The talaqqi method is effective in introducing the Qur’an to young learners and strengthening their understanding of tajwid, though it can be time-consuming and cause boredom. On the other hand, the mutaba’ah method encourages independence, consistent muraja’ah, and increased memorization, although it is influenced by internal student factors and external conditions. Overall, talaqqi is more effective in improving accuracy and retention of memorization, while mutaba’ah enhances fluency and the quantity of students’ memorization.